Analysis of Stunting Determinant Event in Taraweang Village Labakkang District Pangkep - Hermawati Hamalding; Irfan Said; Siti Nurmiati (Study Program of Nutrition, Public Health Faculty, Institut Kesehatan Helvetia, 2020)
Background; Stunting is a condition of failure to thrive in children under five due to chronic malnutrition, especially on the First 1,000 Days of Life (HPK). The condition of failure to thrive in children under five is caused by a lack of nutritional intake in a long time and the occurrence of repeated infections. Objectives; of this study is to find out the analysis of stunting. Method; used was observational with a cross sectional study approach.. The sample in this study was a housewife in Taraweang Village, Labakkang District, Pangkep in 2019. The Determination of sample size by using total sampling where all members of the population are sampled. Results; showed there was a relationship between maternal nutritional knowledge (p = 0.003), diet (p = 0.010), history of breastfeeding (p = 0.000), and history of disease (p = 0.003) with stunting. Conclusion; Maternal nutritional knowledge, diet, history of breastfeeding and history of illness are associated with the occurrence of Stunting